Indywidualna komunikacja z klientem w praktyce funkcjonowania biur podróży w Polsce - Michalska-Dudek, Izabela (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The paper presents both main features and tools of direct marketing. The author describes also questionnaire survey results, assessing forms and individual communication application frequency with clients in the practice of travel agencies in Poland are also described. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (6); 2006; nr 1145, s. 222-229